Failed regulations and school composition: selective admission practices in Chilean primary schools. Issue 5 (3rd September 2017) - Carrasco, Alejandro; Gutiérrez, Gabriel; Flores, Carolina
Abstract: This is an exploratory study about pupil selection. Admission regulations are central to understanding issues of school mix, segregation and educational justice. In Chile, student selection has been intensively discussed but scarcely studied. Using a questionnaire for headteachers ( N  = 581), we explore how school admission processes are organised and implemented within a market-based educational system with a high-stakes testing regime where schools are pushed to use selection practices. Despite the existence of a national (although weak) legal prohibition at the time the survey was conducted, half of the headteachers state that they use some mechanism to select students (play sessions, student testing, or interviews with parents) even when they do not face demand pressures. Exploratory data suggest higher levels of selectivity in subsidised private schools. Regression analysis shows a strong association between 'selectivity' and homogeneous academic intake and social composition. Presumably, the widespread use of selection procedures responds to the structuring force of a double system of educational accountability; strong pressure on performance within a testing regime and where funding depends on enrolments makes selection a fundamental strategy for schools, but which is seriously affecting equality goals.